2010
DOI: 10.1126/scisignal.2000651
|View full text |Cite
|
Sign up to set email alerts
|

A Loss-of-Function Screen Reveals Ras- and Raf-Independent MEK-ERK Signaling During Chlamydia trachomatis Infection

Abstract: Chlamydiae are obligate intracellular bacterial pathogens that have a major effect on human health. Because of their intimate association with their host, chlamydiae depend on various host cell functions for their survival. Here, we present an RNA-interference-based screen in human epithelial cells that identified 59 host factors that either positively or negatively influenced the replication of Chlamydia trachomatis (Ctr). Two factors, K-Ras and Raf-1, which are members of the canonical Ras-Raf-MEK (mitogen-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 49 publications
6
53
0
Order By: Relevance
“…Previous work suggested that rapid phosphorylation of ERK during chlamydial infection is linked to up-regulation of the anti-apoptotic protein MCL-1 (Rajalingam et al, 2008), which we found to be independent of SHC1 (unpublished data). Moreover, in our previous work, activation of both MEK and ERK was shown to be necessary for C. trachomatis at an advanced stage of infection; however, this activation was uncoupled from upstream signaling by RAS and RAF (Gurumurthy et al, 2010). MEK activation is thought to be crucial during infections with H. pylori (Hatakeyama, 2008) and has been shown to be initiated through interaction of CagA with SHP-2 (Higashi et al, 2002), CRK (Suzuki et al, 2005), GRB2 (Mimuro et al, 2002), and c-MET (Churin et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous work suggested that rapid phosphorylation of ERK during chlamydial infection is linked to up-regulation of the anti-apoptotic protein MCL-1 (Rajalingam et al, 2008), which we found to be independent of SHC1 (unpublished data). Moreover, in our previous work, activation of both MEK and ERK was shown to be necessary for C. trachomatis at an advanced stage of infection; however, this activation was uncoupled from upstream signaling by RAS and RAF (Gurumurthy et al, 2010). MEK activation is thought to be crucial during infections with H. pylori (Hatakeyama, 2008) and has been shown to be initiated through interaction of CagA with SHP-2 (Higashi et al, 2002), CRK (Suzuki et al, 2005), GRB2 (Mimuro et al, 2002), and c-MET (Churin et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…C. trachomatis infection leads to extracellular signal-regulated kinase (ERK) activation, followed by the downstream activation of cytosolic phospholipase A2 (cPLA2; Su et al, 2004), the induction of interleukin-8 (IL-8; Buchholz and Stephens, 2008), TNF receptor 1 (TNFR1) shedding (Paland et al, 2008), and stabilization of MCL-1 (Rajalingam et al, 2008). Recent work has revealed that MEK (MAPK/ERK kinase)/ERK activation is independent of RAS/RAF during mid and late C. trachomatis infection (Gurumurthy et al, 2010). Upon activation, MEK1/2 phosphorylates ERK1/2 at specific tyrosine and threonine residues, which then directly phosphorylates a variety of transcription factors including c-JUN, c-MYC, and nuclear factor B (NF-B).…”
Section: Any Bacterial Pathogens Translocate Effectormentioning
confidence: 99%
“…The ERK MAPK signaling pathway appears to be a central regulator for bacterial nutrient acquisition, expression of antiapoptotic factors, and synthesis of proinflammatory cytokines (Su et al 2004;Buchholz and Stephens 2007;Rajalingam et al 2008). Epithelial cells display sustained activation of upstream components of the ERK signaling module including RAS and RAF (Su et al 2004;Gurumurthy et al 2010;Vignola et al 2010). However, this activation of ERK is uncoupled from activated RAS and RAF during infection (Gurumurthy et al 2010;Vignola et al 2010), suggesting multiple signaling pathways are engaged to further Chlamydia replication and intracellular survival.…”
Section: Chlamydial Intracellular Survival Strategiesmentioning
confidence: 99%
“…Epithelial cells display sustained activation of upstream components of the ERK signaling module including RAS and RAF (Su et al 2004;Gurumurthy et al 2010;Vignola et al 2010). However, this activation of ERK is uncoupled from activated RAS and RAF during infection (Gurumurthy et al 2010;Vignola et al 2010), suggesting multiple signaling pathways are engaged to further Chlamydia replication and intracellular survival. Avoidance of cell death and promoting self-survival are complex and very likely temporally regulated strategies deployed during infection and reinfection.…”
Section: Chlamydial Intracellular Survival Strategiesmentioning
confidence: 99%
“…RNA interference screens also have been used to identify host factors important for Chlamydia infection, such as PDGFRβ (11) and the MEK-ERK signaling pathway (12). Despite their widespread use, siRNA screens suffer from off-target effects, and do not always succeed in completely eliminating gene expression.…”
mentioning
confidence: 99%